Hak asasi manusia (human rights) dalam menangani krisis alam sekitar: perspektif Seyyed Hossein Nasr - Zul Azmi Yaakob; Zailan Moris (Universiti Kebangsaan Malaysia, 2012)
Human rights’ are the basic rights and fundamental freedoms. Today’s human rights movements also concern on nature in resolving the environmental crisis. Within the freedom of thought and expression, this trend has extended dramatically in recent years, as many people have been surrounded by massive pollutions such as global warming and water crisis. Many environments have been greatly altered by human activities. On the right track, scholars and scientists have taken risks to test so many ideas and approaches that could lead to exponential changes to improve or even preserve the natural environment. Although ‘human rights’ has been used popularly in recent decades, Seyyed Hossein Nasr argues that the term should be blamed for the environmental crisis we are presently facing. As one of the most important and foremost Muslim philosophers in the world today, Nasr emphasizes that the environmental crisis is created by the crisis of human value in their philosophy of human rights based on human ‘freedom’. Nasr’s writings on human rights can be observed in his Islam and the Environmental Crisis (1990), Islam and the Challenge of the 21st Century (1993) and Religion and the Order of Nature (1996). This semantic study is to show that human rights’ philosophy is too dangerous to nature, tracking on the unconditional absolute rights. Through semantic analysis, the study finds that ‘human rights’ are related to secular philosophy which enthrones the unlimited human freedom, and at the same time against the order of nature as Divine Order.